ADAPTIVE CONTROL OF THOUGHT OUTPUT MODEL: ENGLISH GRAMMAR TEACHING METHOD FOR NON-NATIVE STUDENT A CLASSROOM RESEACH STUDY AT SMA 4 PRAYA - Lalu Dwi Satria Ardiansyah (Lembaga Penelitian dan Pendidikan Mandala, 2017)
This study was aimed at improving the teaching ofgrammar of the eleventgradenon-native students at SMA 4 Prayaby using Adaptive Control of Thought Output Model. This research was action research which consisted of two cycles with threemeetings in each cycle. The subjects of this research were the researcher, the students, the English teacher, and the collaborators. The data collection techniques were observations, interviews, and tests. The data were in the form of qualitative data and quantitative data. The qualitative data were obtained from the field notes and interview transcripts. These data were analyzed using five steps i.e. assembling the data, coding the data, comparing the data, building interpretations, and reporting the outcomes. Meanwhile, the quantitative data were obtained from the pre-test and the post-test scores. These data were analyzed by comparing the mean scores of the pre-test and the post-test. The results of the research show that the use of the Adaptive Control of Thought Output Model in combination with applying various media and activities, such as pictures and games, could improve the teaching of grammar. Based on the qualitative data, the teaching activities become more well-planned and structured. From the group work activities, the students could build their cooperation and improve their participation. The uses of games and pictures could facilitate the students to understand the texts easily. Based on the quantitative data, the students’ grammar comprehension scores increased. The students’ mean score increased from 65.54 to 73.97. The improvement on the students’ mean scores showed that the improvement of the teaching of grammar gave impacts to the students’ achievement. From the data above, it can be concluded that the use of the Adaptive Control of Thought Output Model can improve the teaching of grammar for non native students.